2011
DOI: 10.1590/s1516-35982011000800028
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e características qualitativas da carcaça e da carne de cordeiros terminados em confinamento alimentados com dietas contendo soja grão ou gordura protegida

Abstract: RESUMO -O objetivo foi avaliar o desempenho, as características das carcaças e a qualidade da carne de cordeiros SantaInês, terminados em confinamento, alimentados com dietas contendo 60% de concentrado e enriquecidas com soja grão ou gordura protegida. Os concentrados foram compostos de farelo de soja, milho, farelo de trigo, ureia, núcleo mineral, soja grão

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
2
17
1
13
Order By: Relevance
“…Based on the correlation analyses, the SW of the lambs was not significantly correlated with the HCY, CCY, ICL, SFT, COLOR, MARB or AOL and was negatively correlated (r = -0,08, P <0,05) with the meat TEX (Table 7). These results were corroborated by Goes et al (2012) in the evaluation of the performance and the characteristics of carcasses of heifers fed up to 60% of sunflower cake in their diet; they did not find a correlation between the SW and the ICL. However, Oliveira et al (2010) found a positive correlation between the SW and the ICL.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Based on the correlation analyses, the SW of the lambs was not significantly correlated with the HCY, CCY, ICL, SFT, COLOR, MARB or AOL and was negatively correlated (r = -0,08, P <0,05) with the meat TEX (Table 7). These results were corroborated by Goes et al (2012) in the evaluation of the performance and the characteristics of carcasses of heifers fed up to 60% of sunflower cake in their diet; they did not find a correlation between the SW and the ICL. However, Oliveira et al (2010) found a positive correlation between the SW and the ICL.…”
Section: Resultsmentioning
confidence: 66%
“…Fernandes et al (2011) report that the speed in the reduction of the pH and the final pH affect the water retention capacity, which is a qualitative characteristic of great importance because it affects the appearance, the behavior of the meat during cooking, and the juiciness during chewing. According to Lawrie (2005), the water is maintained by capillarity and is associated with proteinaceous filaments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernandes et al (2011) determined qualitative characteristics of the carcass and meat from Santa Inês lambs finishing in confinement and fed diets containing soybeans or protected fat, and observed better performance in heavier animals and carcasses, without interference in meat quality.…”
Section: Resultsmentioning
confidence: 99%